A Spirituality of Liberation: The Rosary as a Means of Cultivating Simone Weil’s Attention - Faiz Abimanyu Wiguna; Ikhaputri Widiantini (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
This paper explores the interpretation of the Rosary through the philosophical thoughts of Simone Weil, highlighting its potential as a means of cultivating Weil’s living philosophy of “attention,” and by so presenting a spirituality of liberation that attempts to present in whole the twofold image of Weil as both a mystic and a radical. Through Weil’s theory of attention and her two-step philosophical method, which involves reflection on several personal experiences formed through the Rosary, this paper presents a practical formulation of Weil’s moral and religious teaching on attention, especially highlighting the potential for a spirituality of liberation —contributing to the progressive discourse in the philosophy of religion within the Roman Catholic tradition.